Stella Batts : pardon me - Sheinmel, Courtney (Sheinmel, Courtney. Stella Batts, 2012)
"Third-grader Stella Batts needs to find a new best friend after her friend, Willa, moves away, but finding a new best friend is not easy"--Provided by the publisher.